2017
DOI: 10.1155/2017/2409527
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Capacity of Rosemary and Green Tea Extracts to Replace the Carcinogenic Antioxidant (BHA) in Chicken Burgers

Abstract: The present study aimed to evaluate the effect of natural extracts (rosemary and green tea extracts) in frozen storage of chicken burgers. Chicken burger treatments were prepared as follows: control (CON), 20 mg BHA/kg (BHA20), 10 mg green tea extract/kg (GT10), 38 mg green tea extract/kg (GT38), 18.6 mg rosemary extract/kg (RO18), and 480 mg rosemary extract/kg (RO480). Analysis of physicochemical parameters, color, TBAR index, and sensory acceptance were performed at 0, 30, 60, and 120 days of storage at −18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
(36 reference statements)
4
24
2
1
Order By: Relevance
“…The addition of antioxidant in meat products is used to extend the shelf life, increase safety, and prevent damage caused by lipid oxidation (Trindade, Nunes, Contreras‐Castillo, & Felício, ). Synthetic antioxidants have been used to retard or minimize oxidative deterioration of food, but they have raised concerns regarding toxicological aspects and carcinogenic effects (Pires et al, ). In contrast, natural antioxidants have increased their demand in recent years to improve the oxidative stability of the products (Karpińska‐Tymoszczyk, ; Trindade et al, ; Yin, Xing, Zhou, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of antioxidant in meat products is used to extend the shelf life, increase safety, and prevent damage caused by lipid oxidation (Trindade, Nunes, Contreras‐Castillo, & Felício, ). Synthetic antioxidants have been used to retard or minimize oxidative deterioration of food, but they have raised concerns regarding toxicological aspects and carcinogenic effects (Pires et al, ). In contrast, natural antioxidants have increased their demand in recent years to improve the oxidative stability of the products (Karpińska‐Tymoszczyk, ; Trindade et al, ; Yin, Xing, Zhou, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, natural antioxidants have increased their demand in recent years to improve the oxidative stability of the products (Karpińska‐Tymoszczyk, ; Trindade et al, ; Yin, Xing, Zhou, & Zhang, ). Herbs and spices such as rosemary, oregano, sage, green tea, clove, and thyme have been studied in fresh, boiled, fermented, and irradiated meat products (Pires et al, ; Ramalho & Jorge, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BHA and TBHQ are traditional synthetic antioxidants (Pires et al., ). However, there are few studies on the inhibition of CM‐DPPE by antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Arcanjo, Luna, Madruga, and Estevez () found that RES could react with GO in human serum, thereby reducing the accumulation of glycated proteins in the body. Butylated hydroxylanisole (BHA) and tert‐butylhydroquinone (TBHQ) are traditional synthetic antioxidants, and they have ability to remove OH· (Pires et al., ). Therefore, we speculate that EC, ECG, EGC, EGCG, RES, BHA, and TBHQ may inhibit the formation of CM‐DPPE by scavenging OH· or trapping GO.…”
Section: Introductionmentioning
confidence: 99%